(untitled) (International Journal of Geoscience, Engineering and Technology, 2020)
Sanitation is an essential part for human physical, physiological and mental development. It is a public health action, but it is also involved in economic and environmental aspects. The universalization of sanitation is an objective outlined within the National Basic Sanitation Plan, with a goal of serving until the year 2033, but under which there is inefficient investment management. Understanding how sanitation is distributed in the country is a way of assessing what, how and where each part of public sanitation policies works. Data collected through the SNIS suggest greater assistance for sanitation infrastructure in regions with a higher population density and in large commercial and industrial centers, as well as greater investments destined to these areas, mainly the south and southeast regions. The northern and northeastern regions, on the other hand, have the greatest lack of water supply and sanitary sewage, and the least expectation of investments.